Characterization of 6‐propylthiouracil and its interaction with human serum albumin on Au surface by surface‐enhanced Raman scattering. (26th August 2015) - Li, Panfang; Gu, Huaimin
Abstract : In this study, surface‐enhanced Raman scattering (SERS) spectra of 6‐propylthiouracil (6‐PTU) on Au surface and the interaction between 6‐PTU and human serum albumin (HSA) were studied. The Raman bands were assigned by the density functional theory calculations at the B3LYP/6‐311++g(d, p) level. Furthermore, the effects of concentration on the SERS spectra of 6‐PTU were analyzed. It shows that with the changes of the concentrations of 6‐PTU, the SERS spectra of 6‐PTU present significant changes, and it can be concluded that with the changing of concentrations, the orientation of 6‐PTU on Au surface also changes. In addition, the SERS spectra of the interaction between 6‐PTU and HSA show that the binding sites of 6‐PTU to HSA are the functional groups N3H and CO. The information will not only be references to the study of the mechanism of the interaction between drugs and blood plasma or serum albumin but also a guidance to understand the metabolism of drugs in human body. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Key findings are as follows. The experimental Raman spectra and density function theory calculations give further confirmation of the assignments of Raman bands of 6‐propylthiouracil in solid state. The result of surface‐enhanced Raman scattering spectra of 6‐propylthiouracil on Au surface shows that the propyl and S atom of 6‐propylthiouracil molecule are closer to Au surface than O atom. The interaction between 6‐propylthiouracil and human serum albumin was investigated by the surface‐enhanced Raman scattering technique with molecular docking and it shows that the binding sites of 6‐propylthiouracil to human serum albumin are groups N3H and CO.